Surface deformations of 24 January 2020 Sivrice (Elazığ)–Doğanyol (Malatya) earthquake (Mw = 6.8) along the Pütürge segment of the East Anatolian Fault Zone and its comparison with Turkey’s 100-year-surface ruptures - Tatar, Orhan; Sözbilir, Hasan; Koçbulut, Fikret; Bozkurt, Erdin; Aksoy, Ercan; Eski, Semih; Metin, Yüksel (Springer Science and Business Media B.V., 2020)
On Friday, January 24, 2020 at 20.55:11 local time (17:55 UTC), an earthquake with a magnitude of Mw = 6.8 has occurred in Sivrice district of Elazığ (Eastern Turkey). Focal mechanism solution is consistent with pure left-lateral strike-slip faulting; the location of the epicenter and fault mechanism suggest deformation along the Pütürge segment of the East Anatolian Fault Zone. A 10-day fieldwork was carried out along the Pütürge segment to study surface deformation; the geometry of the surface rupture and other seismic geomorphological structures were mapped and studied in detail. The field data are also correlated with satellite images. This paper, therefore, presents classification of seismic geomorphological structures and discuss intimate relationship between fault geometry and stress field in the region. Seismic geomorphological deformation and related features of the Sivrice (Elazığ) earthquake are observed in the area between Gezin (Elazığ) and Ormaniçi (Pütürge) villages; they are classified into two as seismotectonic and seismo-gravitational features. Field observations confirm that seismo-gravitational structures develop along both Gezin-Sivrice–Doğanbağı and Doğanbağı–Çevrimtaş–Ilıncak–Koldere–Ormaniçi sections of the Pütürge segment, while surface rupture is mapped as seismotectonic structure only along the Doğanbağı–Çevrimtaş–Ilıncak–Koldere–Ormaniçi section. Small-scale landslides, rock falls, feather cracks along asphaltic roads, and laterally discontinues ground failure-related features are common seismo-gravitational structures that developed along the fault zone. In addition, small-scale lateral spreading and liquefaction structures are common especially in areas where fault-perpendicular streams meet the Karakaya Dam reservoir. The surface rupture is mapped as stepping and overlapping en échelon fractures along elongated pressure ridges between Çevrimtaş and Doğanbağ villages, to northwest of Ilıncak village, along 1.5-km-long pressure ridge between Topaluşağı and Doğanyol, across the elongated hill that developed on an alluvial fan to the northwest of Doğanyol and in the area between Koldere and Ormaniçi villages. Surface fractures deforming the pressure ridges are all aligned parallel to the long axes of the ridges and display reverse components that give rise to small-scale pop-up structures. Interferometric SAR (DInSAR) studies indicate a 10-cm uplift in the northwestern block of the fault and a 6-cm subsidence in the southeast block. The difference in vertical movements between two blocks of the fault is interpreted to suggest that at least 30-km-long section of the Pütürge segment in the area between southwest of Sivrice and Pütürge is broken during the main shock. Although the focal mechanism solution of the main shock gives pure left-lateral strike-slip faulting, there is no significant left-lateral displacement observed during the fieldwork. This can be explained by the following: (1) left-lateral strike-slip displacement was not able to reach the surface; (2) left-lateral torque movement of the fault around a vertical axis during the earthquake, (3) restraining bend nature of the Pütürge segment, or (4) the presence of Pütürge metamorphics along the fault strike. It is also important to note that along most part of the Pütürge segment where surface rupture is observed, talus, colluvial or alluvial fan sediments are exposed; unconsolidated and/or poorly consolidated nature of these sediments may also be counted as one of the main reason for not observing horizontal displacement on the surface. When we compare these surface deformations with the surface ruptures that occurred in the last 100 years in Turkey, we suggest that the formation of the surface deformations is variable depending on: (1) the fault type and the state of regional stress, (2) the magnitude of the earthquake, (3) the duration time of the earthquake and (4) the geomorphologic feature of landscape in relation to the lithologic and structural features of the rock units along the active fault zone. © 2020, Springer Nature Switzerland AG.
Keywords: East Anatolian Fault Zone; Pütürge segment; Seismic geomorphology; Sivrice (Elazığ)–Doğanyol (Malatya) earthquake; Turkey’s 100-year-surface ruptures